SIFAT FISIK DAN KIMIA TANAH PADA LAHAN AGROFORESTRI DI DESA SULI KECAMATAN BALINGGI KABUPATEN PARIGI MOUTONG - Zikrullah, Eki; Wardah, Wardah; Umar, Husain (Universitas Tadulako, 2015)
The soil function utizilations as the plants media started since human civilization turns from nomadic collecting food to live permanent living in settlement begin to moving food plant/non food to the close area with the place they live. In the next stage, the understandingof soil function grows as nutrient supplier for the plants it self so the productions would be reached depends on the soil capacity in providing the nutrient (soil fertility). This research aims to find out the characteristics of physical and chemistry on soil of agroforestry land nyatoh based, cacao based and agroforestry complex in Suli village Balinggi sub district Parigi mouton regensi during Mei ti July 2014. The method employed was field survey, soil sample, soil sample analysis in laboratory and data analysis.The location selection was done through purposive sampling. The result indicates that physical and chemistry soil characteristics in each agroforestry land in the village has 10 colors of yellow-red, permeability value classified little late on nyatoh based, cacao based classified little late as well and on agroforestry land with 15 cm depth and classified very late on 30 cm depth. The porosity value of each usage type of land classified moist with bulk density value quite enough and low organic material value in each land usage type and pH value on agroforestry land nyatoh based in 15 cm dept shows netral pH but in 30 cm dept pH becomes little alkalis then in agroforestry land cacao based and agroforestri complex pH is sour. Keywords: Soil, Physical and Chemistry on Soil, Agroforestry